The image of medieval Ukraine’s culture on the pages of "Chteniya v istoricheskom obshchestve Nestora Letopistsa" - I. H. Adamska (Ukrainian Cultural Studies, 2020)
The Historical Society of Nestor the Chronicler was one of the organizations in the second half of 19th – the first half of 20th century which researched the culture of Ukraine. Members of the society published their studies in various periodicals. Beginning from the year 1888 their annual journal "Chteniya v Istoricheskom obshchestve Nestora Letopistsa" appeared regularly. The purpose of this article are to identify topics from the cultural history of the 10th -16th century which were of interest for the members of the society, as well as studies published by them on the journal pages. The other purpose is to systematize interpretations of problems of cultural history raised by the members, and to define the role which was given to the medieval culture in the development of this region by the above-mentioned researchers. It was found, as a result of the study, that beginning from the second half of the 19th century the scholars increasingly turned to the topics predeceasing the Cossack period for emphasising the cultural originality of lands of Southern Ruthenia (Rus’). Researchers turned to the study of monuments of literature to discover local traditions and possible foreign influences. The identified borrowings were often interpreted that they had reflected the existing diversity of the language and culture. Yet there were also some attempts to prove a close connection with the culture of Northern Ruthenia (so called: "Great Russian" culture) on the basis of the established facts. On occasion of the 900th anniversary of the baptism of Ruthenia the researcher intensified their studies on the history of religions. The most attention was paid to the adoption of the Eastern Christianity by Eastern Slavs and the development of Orthodoxy in the area they inhabited. However, researchers were also interested in the history of the Roman Catholic Church, Judaism, Protestantism and their influence on the culture of the region. The members of the society discovered andanalysed landmarks from the Middle Ages and from the beginning of Early Modern times. Artworks from this period survived worst of all. The researchers studied sacral buildings, the interior decoration of temples, icons, as well as what were left from the secular architecture, including castles and fortifications. They also tried to identify distinctive elements of artistic development and possible foreign influences. In addition, cultural relations of Ruthenia with other countries were studied. The special attention was paid to the marriage unions, to the connection between economic and cultural interactions and to the religious factor of the relations between various states. The image of the culture of Middle Edges as an important period of Ukraine’s cultural history was being created by publishing research results on the pages of the journal.